2017
DOI: 10.1152/ajprenal.00246.2016
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensinogen import in isolated proximal tubules: evidence for mitochondrial trafficking and uptake

Abstract: The renal proximal tubules are a key functional component of the kidney and express the angiotensin precursor angiotensinogen; however, it is unclear the extent that tubular angiotensinogen reflects local synthesis or internalization. Therefore, the current study established the extent to which angiotensinogen is internalized by proximal tubules and the intracellular distribution. Proximal tubules were isolated from the kidney cortex of male sheep by enzymatic digestion and a discontinuous Percoll gradient. Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…However, whereas internalization has been demonstrated 30 , a mechanism of how ANGII may leave the vesicles is not known so far. Also, angiotensinogen appears to be internalized 31 . On the other hand, Singh et al demonstrated that ANG can be generated intracellularly in the absence of extracellular components of the RAS in neonatal cardiomyocytes, and that the system can be stimulated by high glucose 32 .…”
Section: Discussionmentioning
confidence: 99%
“…However, whereas internalization has been demonstrated 30 , a mechanism of how ANGII may leave the vesicles is not known so far. Also, angiotensinogen appears to be internalized 31 . On the other hand, Singh et al demonstrated that ANG can be generated intracellularly in the absence of extracellular components of the RAS in neonatal cardiomyocytes, and that the system can be stimulated by high glucose 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The possible presence of a mitochondrial RAS was suggested after observing different RAS components such as renin, ACE, and Ang II in cells from adrenal gland, kidney or cerebellar cortex, particularly using electron microscopy or uptake of labelled Ang II studies ( Erdmann et al, 1996 ; Peters et al, 1996 ; van Kats et al, 2001 ). More recently the presence of a number of RAS components such as Ang I, Ang II, and Ang 1–7 was confirmed in mitochondria isolated from kidney cortex ( Wilson et al, 2016 , 2017 ). Mitochondrial angiotensins may be imported from the cytoplasm.…”
Section: The Mitochondrial Rasmentioning
confidence: 91%
“…Obviously, endocytosis should then not result in angiotensinogen destruction. According to Wilson et al [58], internalized angiotensinogen traffics intact to the mitochondria in isolated proximal tubules. However, given the absence of intracellular angiotensin generation [4], the implications of this finding are unclear.…”
Section: Megalin and Renal Angiotensin Productionmentioning
confidence: 99%